A Buccal Mucosal Oximeter Accurately Measures Arterial Oxyhemoglobin Saturation - Snow C; Magnison-Benoit S; Pun M; Tripp TR; Clarke A; Berghmans S; Hansen B; Transfiguracion L; Adatia S; Rawling JM; Roy S; Di Simone G; et al. (Medical Devices: Evidence and Research, 2025)
Connor Snow,1– 3 Shane Magnison-Benoit,1– 3 Matiram Pun,1– 3 Thomas R Tripp,1– 3 Aimee Clarke,1– 3 Sophie Berghmans,1– 3 Bradley Hansen,1– 3 Leo Transfiguracion,4 Saleema Adatia,5 Jean M Rawling,6 Steven Roy,7,8 Giovanni Di Simone,9 Ming-Lai Lai,9 Erin V Mosca,9 John E Remmers,9 Marc J Poulin1– 3,8,10,11 1Department of Physiology and Pharmacology, Cumming School of Medicine, University of Calgary, Calgary, Alberta, Canada; 2Hotchkiss Brain Institute, Cumming School of Medicine, University of Calgary, Calgary, Alberta, Canada; 3Faculty of Kinesiology, University of Calgary, Calgary, Alberta, Canada; 4Department of Anesthesia, Alberta Health Services, Calgary, Alberta, Canada; 5Symmetry Dental, Calgary, Alberta, Canada; 6Department of Family Medicine, University of Calgary, Calgary, Alberta, Canada; 7Department of Critical Care Medicine, University of Calgary, Calgary, Alberta, Canada; 8O’Brien Institute for Public Health, Cumming School of Medicine, University of Calgary, Calgary, Alberta, Canada; 9ProSomnus Sleep Technologies, Pleasanton, CA, USA; 10Libin Cardiovascular Institute of Alberta, Cumming School of Medicine, University of Calgary, Calgary, Alberta, Canada; 11Department of Clinical Neurosciences, Faculty of Medicine, University of Calgary, Calgary, Alberta, CanadaCorrespondence: Marc J Poulin, HMRB-210, 3330 Hospital Drive NW Cumming School of Medicine, University of Calgary, Calgary, Alberta, T2N 4N1, Canada, Tel +1 403-220-8372, Email poulin@ucalgary.caPurpose: While arterial oxyhemoglobin saturation (SaO2) decreases during sleep in many patients with sleep apnea and pulmonary diseases, personalized oximeters suitable for multi-night monitoring of SpO2 are not readily available. The present report describes a custom buccal mucosal intraoral oximeter that might provide the opportunity for such long-term monitoring given its strong accuracy in measuring SpO2 over a range of clinically relevant hypoxemia.Patients and Methods: The intraoral buccal mucosal oximeter was constructed by encapsulating a reflectance pulse oximeter in an overlay of the maxillary dentition. Accuracy was assessed during non-motion conditions in normal participants (n = 12) made progressively hypoxic by decreasing the partial pressure of end-tidal oxygen (PETO2). CO-oximeter values of SaO2 from arterial blood constituted the “gold standard” for comparison with the buccal mucosal oximeter’s values. The oximeter’s pulse rate and an electrocardiogram (ECG) determined heart rate were also compared.Results: Analysis of 325 paired SaO2 values from the CO-oximeter and buccal mucosal oximeter yielded the following: r = 0.95; bias = 0.72; and accuracy root-mean-square (ARMS) = 2.94%. Results from the pulse rate/ECG analysis were: r = 0.99; bias = 0.30; and ARMS = 2.08 bpm.Conclusion: These results reveal robust accuracy of the buccal mucosal oximeter measurement of SaO2 and pulse rate, as shown by good agreement with a “gold standard” over a wide range of arterial hypoxemia. Such clinically acceptable accuracy indicates that this novel reflectance oximeter may prove useful in management of patients with sleep-induced hypoxemia by allowing for long-term monitoring of SaO2.Keywords: hypoxia, oximetry, intraoral pulse oximeter, respiratory monitoring, obstructive sleep apnea, remote patient monitoring